6 - Les résistances à la colonisation française en Afrique noire (1871-1914): by Christophe Wondji - Christophe Wondji (Africa Development, 1993)
The creation between 1871 and 1914 of Francophone Western Africa and Francophone Eastern Africa was achieved through two processes: conquest then complete domination of the peoples. However the peoples strongly resisted both politically and militarily. In the Sudan-Sahel area, Islam played a key role in the resistance to French conquest by devising the military logistics and diplomatic channels. African kings also used the wars and diplomacy for their political gains and strategic alliances. That was what Elhadji Omar, Samori, Gbehanzin and Rabah did to fight Bouet-Willaumez, Faidherbe, Borgnis-Desbordes, Gallieni, Archinard and Gentil. After the defeat of the more powerful kings the struggle for resistance was continued by the less powerful ones. This happened in many segmentary societies and some revolts against social and economic exploitations. However in some coastal and forest areas, the local resistance was weak.